Keamanan dan Kenyamanan Wisatawan dalam Pengelolaan Risiko di Kawasan Wisata Religi Sam Poo Kong - Desika Nur Jannah; Sugiarto Sugiarto; Amin Kiswantoro; Fera Dhian Anggraini (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Sam Poo Kong Religious Tourism Area in Semarang City is a spiritual and cultural tourism destination with a relatively high number of visitors, thereby requiring effective operational risk management to ensure tourists’ safety and comfort. In the context of religious tourism, safety and comfort are not limited to physical protection, but also encompass psychological and emotional experiences that shape a sense of tranquility, security, and inner balance among visitors. This study aims to analyze tourists’ safety and comfort in the implementation of operational risk management at the Sam Poo Kong Religious Tourism Area. A qualitative research approach was employed using in-depth interviews with tourists and site managers, complemented by participatory observation. Data were analyzed through data reduction, thematic categorization, and interpretative analysis. The findings reveal two main aspects. First, informative, responsive, and humanistic public services and communication play a crucial role in building tourists’ trust and perceptions of safety and comfort. Second, environmental spirituality, manifested through a sacred atmosphere, religious symbols, and cultural values, contributes significantly to visitors’ emotional security and psychological comfort. The novelty of this study lies in emphasizing that operational risk management in religious tourism destinations should not be confined to technical aspects alone, but must be integrated with service quality, public communication, and environmental spirituality as a comprehensive risk management strategy.